Fast ion conductor interface compatibilization ionic conductive binder for lithium battery and preparation method thereof
By using modified inorganic fast ion conductor powder and unsaturated monomer for emulsion copolymerization and lithiation neutralization in lithium battery electrode binder, a high-performance fast ion conductor interface capacity-enhancing ion conductive binder was prepared, which solved the problem of traditional binders hindering lithium ion migration and significantly improved the rate performance and cycle stability of lithium batteries.
Patent Information
- Application Number
- CN202411755309.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional lithium battery electrode binders hinder the migration of lithium ions, resulting in poor rate performance and difficulty in achieving fast charging.
A high-performance fast ion conductor interface capacitance ion conductive adhesive is prepared by emulsion copolymerization and lithiation neutralization of the inorganic fast ion conductor powder modified with double bond group coupling agent and a variety of unsaturated monomers.
It significantly improves the transmission capacity of lithium ions, improves the rate performance of lithium batteries, and adapts to the volume deformation of the battery during charging and discharging through high toughness, improving cycle stability.
Smart Images

Figure CN119529716A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a fast ion conductor interface capacity increasing ion conductive adhesive for lithium batteries and a preparation method thereof. Background Art
[0002] The booming development of mobile electronic devices and electric vehicles requires not only high energy density of lithium batteries, but also better rate performance. However, traditional electrode binders do not have the function of transmitting lithium ions, so the binder network formed in the electrode has a significant obstacle to the migration of lithium ions, which is an important factor leading to the poor rate performance of existing lithium batteries and the difficulty in achieving fast charging. Developing ion conductive binders is an effective way to solve the above problems.
[0003] Recently, some patents have disclosed inventions for preparing ion-conductive adhesives by performing lithium-ion conductive modification on polymer matrices. Patent CN 202311407648.6 introduces cationic polymer side chains on the main chain of polyvinylidene fluoride-based materials by ultraviolet light-induced graft polymerization. The cationic structure can bind to anions in the electrolyte to promote the transmission of lithium ions. Patent CN 202211153228.5 achieves simultaneous improvement of bonding ability and ion conductivity by grafting carboxylic acid groups on styrene butadiene styrene block copolymers and then lithiation. However, there are problems of high difficulty in molecular design and complex preparation process in the modification based on the polymer matrix. In contrast, blending fillers with lithium-ion conductive function with polymer matrices is a more scalable production potential approach to preparing ion-conductive adhesives, but the uneven dispersion and sedimentation problems caused by poor compatibility between fillers and matrices must be solved. Summary of the invention
[0004] In view of the problems existing in the prior art, the present application provides a fast ion conductor interface capacity-enhancing ion conductive adhesive for lithium batteries and a preparation method thereof. The ion conductivity of the adhesive film is higher than 0.10 mS / cm, and the elongation at break exceeds 100%. The adhesive is obtained by emulsion copolymerization and lithiation neutralization of an inorganic fast ion conductor powder modified with a coupling agent containing a double bond group and a plurality of unsaturated monomers. The adhesive has a dual lithium ion transmission channel, which greatly improves the lithium ion transmission capacity of the adhesive and significantly improves the rate performance of the lithium battery. At the same time, the high toughness gives it the ability to adapt to the volume deformation during the charging and discharging process of the sulfur positive electrode and the silicon negative electrode, which is beneficial to improving the cycle stability of the lithium battery.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries is provided. The fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries is mainly formed by emulsion copolymerization and lithiation neutralization of four components A, B, C, and D, wherein component A is an inorganic fast ion conductor powder modified by a coupling agent containing a double bond group, which is 3 to 10 parts by weight; component B is a lithiation-capable unsaturated monomer, which is 5 to 15 parts by weight; component C is an acrylate unsaturated monomer, which is 30 to 60 parts by weight; and component D is an unsaturated monomer with excellent resistance to organic electrolytes, which is 25 to 40 parts by weight.
[0006] Wherein, the inorganic fast ion conductor is one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, and lithium lanthanum zirconium oxide.
[0007] The coupling agent containing double bond groups is one of vinyl dimethyl chlorosilane, vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri (β-methoxyethoxy) silane, and diisopropyl diacryloyl titanate.
[0008] The lithiation-capable unsaturated monomer is one of acrylic acid, methacrylic acid and 2-ethylacrylic acid.
[0009] The acrylic acid ester unsaturated monomer is one of ethyl acrylate, butyl acrylate and isooctyl acrylate.
[0010] The unsaturated monomer with excellent resistance to organic electrolyte is one of styrene and acrylonitrile.
[0011] The second aspect of the present invention provides a method for preparing the fast ion conductor interface capacity increasing ion conductive binder for lithium battery, comprising the following steps:
[0012] (1) Inorganic fast ion conductor powder is added to a mixture of ethanol and deionized water. After ultrasonic dispersion, a coupling agent containing a double bond group is slowly added dropwise under mechanical stirring. The mixture is reacted at 30-60 °C for 12-36 hours. After the reaction is completed, the inorganic fast ion conductor powder modified with a coupling agent containing a double bond group is obtained by washing with ethanol, filtering, and drying. (2) 3-10 parts by weight of double bond modified inorganic fast ion conductor powder, 5-15 parts by weight of lithiation-capable unsaturated monomer, 40-60 parts by weight of acrylate unsaturated monomer, 25-45 parts by weight of unsaturated monomer with excellent resistance to organic electrolyte, 1-2 parts by weight of crosslinking agent and 2-5 parts by weight of surfactant are added into deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature is raised to 40-60° C., and then 2-3 parts by weight of redox initiator is added. After reacting for 2-4 hours, 1-2 parts by weight of redox initiator is added. After continuing to react for 2-4 hours, an organic-inorganic hybrid emulsion is obtained. Finally, 0.5-2 mol / L of lithium hydroxide aqueous solution is added dropwise to perform lithiation neutralization to pH=7-8 to obtain a fast ion conductor interface capacity increasing ion conductive binder for lithium batteries with a solid content of 8 wt%-15 wt%.
[0013] Wherein, the mass ratio of the inorganic fast ion conductor powder to ethanol is 1:10-25.
[0014] The mass ratio of the inorganic fast ion conductor powder to the coupling agent containing double bond groups is 1:0.02-0.05. The mass ratio of the coupling agent containing double bond groups to deionized water is 1:10-15.
[0015] The crosslinking agent is one of divinylbenzene, ethylene glycol diacrylate and 1,4-butanediol diacrylate.
[0016] The emulsifier is one of sodium dodecyl sulfate, ammonium nonylphenol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate.
[0017] The oxidizing component of the redox initiator is one of potassium persulfate, ammonium persulfate, and hydrogen peroxide; the reducing component of the redox system initiator is one of sodium thiosulfate, sodium bisulfite, and ferrous sulfate; the molar ratio of the oxidizing component to the reducing component of the initiator is 1:0.4~1.
[0018] Compared with the prior art, the beneficial effects of the present invention include at least:
[0019] (1) The fast ion conductor interface capacity increasing ion conductive binder for lithium battery described in the present invention is a method of preparing an organic-inorganic hybrid emulsion by double-bond surface modification of inorganic fast ion conductor powder and in-situ emulsion polymerization. This solves the problem of uneven dispersion and sedimentation of inorganic fast ion conductor powder caused by simple blending of composite emulsions, and significantly improves the dispersion stability and mechanical properties of the ion conductive binder.
[0020] (2) The fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries described in the present invention comprises a dual lithium ion conductive channel formed by a lithiated polymer matrix and a fast ion conductor, which endows the binder with high ion conductivity, thereby significantly improving the rate performance of lithium batteries.
[0021] (3) The fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries described in the present invention contains a flexible copolymer component, which gives it the ability to adapt to the volume deformation of the sulfur positive electrode and the silicon-based negative electrode during the charging and discharging process. At the same time, it contains rich polar functional groups (cyano, ester, carboxyl), has a strong adsorption capacity for lithium polysulfide in the sulfur positive electrode, and can significantly inhibit its shuttle effect; and has an excellent bonding effect on the silicon-based negative electrode. Thereby improving the cycle stability of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The following are scanning electron microscope images of (a) the ion conductive adhesives of Example 1 and (b) Comparative Example 2.
[0023] Figure 2 The rate performance of the sulfur positive electrode prepared using the ion conductive binder described in Example 1, Comparative Example 1 and Comparative Example 2.
[0024] Figure 3 The rate performance of the silicon-carbon negative electrode prepared using the ion conductive binder described in Example 1, Comparative Example 1 and Comparative Example 2.
[0025] Figure 4 The cycle performance of the lithium-sulfur battery prepared using the ion conductive binder described in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0026] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with embodiment. It should be understood by those skilled in the art that the embodiment is only to help understand the present invention and should not be regarded as a specific limitation of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] In this embodiment, a fast ion conductor interface capacity-enhancing ion conductive binder for lithium battery is provided, and the fast ion conductor interface capacity-enhancing ion conductive binder is prepared by the following steps:
[0029] (1) 2 g of lithium aluminum titanium phosphate was added to a mixture of 50 mL of ethanol and 1 mL of deionized water. After ultrasonic dispersion, 80 mg of vinyldimethylsilyl chloride was slowly added dropwise under mechanical stirring. After reacting at 50 °C for 24 hours, the mixture was washed with ethanol, filtered, and dried to obtain lithium aluminum titanium phosphate powder modified with a coupling agent containing a double bond group.
[0030] (2) 0.5 g of the lithium aluminum titanium phosphate powder modified with the above-mentioned coupling agent containing double bond groups, 0.93 g of methacrylic acid, 4.8 g of butyl acrylate, 3.6 g of acrylonitrile, 0.1 g of divinylbenzene, and 0.23 g of sodium dodecyl sulfate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 50°C, and then 0.16 g of ammonium persulfate and 0.08 g of sodium bisulfite aqueous solution were added. After reacting for 3 hours, 0.09 g of ammonium persulfate and 0.05 g of sodium bisulfite aqueous solution were added. The reaction was continued for 2 hours to obtain an organic-inorganic hybrid emulsion. Finally, 1 mol / L of lithium hydroxide aqueous solution was added dropwise for lithium neutralization to pH = 7-8 to obtain a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries with a solid content of 12 wt%.
[0031] from Figure 1 As can be seen from the scanning electron microscope photograph of a, the double-bond modified lithium aluminum titanium phosphate in the hybrid emulsion of Example 1 is uniformly wrapped by the polymer latex without agglomeration. This is attributed to the in-situ polymerization of the unsaturated monomer on the surface of the double-bond modified lithium aluminum titanium phosphate powder, thereby improving the dispersion stability of the lithium aluminum titanium phosphate powder in the binder.
[0032] The applicant further uses the fast ion conductor interface capacity-enhancing ion conductive binder prepared in this embodiment in the preparation of sulfur positive electrodes of lithium-sulfur batteries and silicon-carbon negative electrodes of lithium batteries.
[0033] Preparation of sulfur positive electrode sheet and assembly of button-type lithium-sulfur battery: The sulfur-carbon composite material, conductive agent Super P (conductive carbon black), and ion conductive binder are dispersed in deionized water in a ratio of 8:1:1, ball milled for 6 hours to obtain a uniform slurry, then coated on aluminum foil and dried in a vacuum oven at 60°C for 12 hours. The dried electrode sheet is cut into discs with a diameter of 12 mm using a punching machine. The applicant further assembled the above discs into a CR2025 button-type lithium-sulfur battery in an argon-filled glove box (water value <0.1 ppm, oxygen value <0.1 ppm): the lithium sheet is used as the negative electrode, the diaphragm is a commercial polypropylene diaphragm, the electrolyte is a mixed solution of dioxolane dissolved with 1 mol / L lithium bistrifluoromethylsulfonyl imide) and dimethyl ether (the volume ratio of the two solvents is 1:1), and 1 wt% lithium nitrate is used as an additive to assemble a button-type lithium-sulfur battery. After the assembled battery was left to stand for 24 hours, the electrochemical performance test was carried out at a constant temperature of 25°C using the Xinwei test system.
[0034] Preparation of silicon-based negative electrode sheet and assembly of button-type lithium-ion half-cell: Add appropriate amount of deionized water to commercial silicon-carbon composite material (theoretical specific capacity 650 mAh / g), conductive agent Super P (conductive carbon black), and ion conductive binder in a ratio of 90:5:5, stir thoroughly in a planetary vacuum mixer to obtain a uniform slurry, then coat it on copper foil and dry it in a vacuum oven at 120°C for 12 hours. The dried electrode sheet is cut into discs with a diameter of 12 mm using a punching machine. The applicant further assembled the above discs into a CR2025 button-type lithium-ion half-cell in an argon-filled glove box (water value <0.1 ppm, oxygen value <0.1 ppm): lithium sheet is used as the counter electrode, the diaphragm is a commercial polypropylene diaphragm, the electrolyte is a mixed solution of ethylene carbonate and diethyl carbonate dissolved with 1 mol / L lithium hexafluorophosphate (the volume ratio of the two solvents is 1:1), and 10% fluoroethylene carbonate is used as an additive to assemble a silicon-carbon negative electrode half-cell. After the assembled battery was left to rest for 24 hours, the electrochemical performance was tested using the Xinwei testing system at a constant temperature of 25°C.
[0035] from Figure 2 From the rate performance tests of the lithium-sulfur batteries prepared in Example 1 and Comparative Examples 1 and 2, it can be seen that the rate performance of the lithium-sulfur battery prepared using the fast ion conductor interface capacitating ion conductive binder described in Example 1 is better, and the discharge capacity of 915 mAh / g is still maintained at a cycle rate of 4 C. The discharge capacity of the lithium-sulfur batteries assembled in Comparative Examples 1 and 2 at a rate of 4 C is only 707 mAh / g and 225 mAh / g, respectively. At the same time, from Figure 3From the rate performance test of the silicon-carbon negative electrode half-cell assembled in Example 1 and Comparative Examples 1 and 2, it can be seen that the rate performance of the silicon-carbon negative electrode half-cell prepared using the fast ion conductor interface capacity-enhancing ion conductive binder described in Example 1 is better, and it exhibits a higher discharge specific capacity at a current density of 0.1 C to 1 C, up to 386 to 645 mAh / g. In contrast, the silicon-carbon negative electrode half-cells assembled in Comparative Examples 1 and 2 only exhibited discharge specific capacities of 333 to 639 mAh / g and 263 to 628 mAh / g, respectively, at a current density of 0.1 C to 1 C. The above performance comparison is due to the fact that the invented binder contains a dual lithium ion conductive channel formed by a lithiated polymer matrix and a fast ion conductor, which gives the binder good ionic conductivity. At the same time, the uniform distribution of the components in the binder improves the adhesion, which is also beneficial to the electrochemical performance of the lithium battery.
[0036] from Figure 4 In the cycle performance test of the lithium-sulfur batteries assembled in Example 1 and Comparative Examples 1 and 2, it can be seen that the button-type lithium-sulfur battery assembled using the binder of Example 1 has a capacity retention rate of up to 80.4% after 150 cycles of charge and discharge, which is significantly better than 58.5% and 38.7% of Comparative Examples 1 and 2. This substantial improvement in cycle stability can be attributed to the synergistic effect of the abundant polar functional groups (cyano, ester, carboxyl) and dual lithium ion conductive channels in the invented binder, because the significantly improved lithium ion transport capacity in the positive electrode can promote the rapid conversion of lithium polysulfide captured by the polar groups, thereby inhibiting the shuttle effect.
[0037] Example 2
[0038] In this embodiment, a fast ion conductor interface capacity-enhancing ion conductive binder for lithium battery is also provided, and the fast ion conductor interface capacity-enhancing ion conductive binder is prepared by the following steps:
[0039] (1) 2 g of lithium lanthanum titanate was added to a mixture of 25 mL of ethanol and 0.4 mL of deionized water. After ultrasonic dispersion, 40 mg of vinyltrimethoxysilane was slowly added dropwise under mechanical stirring. After reacting at 30 °C for 36 hours, the mixture was washed with ethanol, filtered, and dried to obtain lithium lanthanum titanate powder modified with a coupling agent containing a double bond group.
[0040] (2) 1 g of the above-mentioned lithium lanthanum titanyl powder modified with a coupling agent containing a double bond group, 0.47 g of acrylic acid, 4.6 g of ethyl acrylate, 4.3 g of acrylonitrile, 0.15 g of ethylene glycol diacrylate, and 0.19 g of ammonium nonylphenol polyoxyethylene ether sulfate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 40°C, and then 0.2 g of potassium persulfate and 0.08 g of sodium thiosulfate aqueous solution were added. After reacting for 4 hours, 0.14 g of potassium persulfate and 0.05 g of sodium thiosulfate aqueous solution were added. The reaction was continued for 4 hours to obtain an organic-inorganic hybrid emulsion. Finally, 0.5 mol / L of lithium hydroxide aqueous solution was added dropwise for lithium neutralization to pH = 7-8 to obtain a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries with a solid content of 15 wt%.
[0041] The applicant further used the fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries of this embodiment in the preparation of the sulfur positive electrode of lithium-sulfur batteries and the silicon-carbon negative electrode of lithium-ion batteries, and further assembled the electrode pieces into button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells to test the lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode. The preparation of the sulfur positive electrode and silicon-carbon negative electrode, and the assembly method of the button-type lithium-sulfur battery and silicon-carbon negative electrode half-cell are the same as in Example 1.
[0042] Example 3
[0043] In this embodiment, a fast ion conductor interface capacity-enhancing ion conductive binder for lithium battery is also provided, and the fast ion conductor interface capacity-enhancing ion conductive binder is prepared by the following steps:
[0044] (1) 2 g of lithium lanthanum zirconium oxide was added to a mixture of 62.5 mL of ethanol and 1.5 mL of deionized water. After ultrasonic dispersion, 100 mg of vinyltriethoxysilane was slowly added dropwise under mechanical stirring. After reacting at 60 °C for 12 hours, the lithium lanthanum zirconium oxide powder modified with a coupling agent containing a double bond group was obtained by washing with ethanol, filtering and drying.
[0045] (2) 0.3 g of the above-mentioned lithium lanthanum zirconium oxide powder modified with a coupling agent containing a double bond group, 1.4 g of 2-ethyl acrylic acid, 5.6 g of isooctyl acrylate, 2.3 g of styrene, 0.19 g of divinylbenzene, and 0.47 g of sodium dodecylbenzene sulfonate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 60°C, and 0.09 g of ammonium persulfate and 0.09 g of sodium bisulfite aqueous solution were added. After reacting for 2 hours, 0.09 g of ammonium persulfate and 0.09 g of sodium bisulfite aqueous solution were added. The reaction was continued for 3 hours to obtain an organic-inorganic hybrid emulsion. Finally, 2 mol / L of lithium hydroxide aqueous solution was added dropwise for lithium neutralization to pH = 7-8 to obtain a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries with a solid content of 8 wt%.
[0046] The applicant further used the fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries of this embodiment in the preparation of the sulfur positive electrode of lithium-sulfur batteries and the silicon-carbon negative electrode of lithium-ion batteries, and further assembled the electrode pieces into button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells to test the lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode. The preparation of the sulfur positive electrode and silicon-carbon negative electrode, and the assembly method of the button-type lithium-sulfur battery and silicon-carbon negative electrode half-cell are the same as in Example 1.
[0047] Example 4
[0048] In this embodiment, a fast ion conductor interface capacity-enhancing ion conductive binder for lithium battery is also provided, and the fast ion conductor interface capacity-enhancing ion conductive binder is prepared by the following steps:
[0049] (1) 2 g of lithium lanthanum zirconium oxide was added to a mixture of 50 mL of ethanol and 1.2 mL of deionized water. After ultrasonic dispersion, 60 mg of vinyl tri(β-methoxyethoxy)silane was slowly added dropwise under mechanical stirring. After reacting at 40 °C for 24 hours, the lithium lanthanum zirconium oxide powder modified with a coupling agent containing a double bond group was obtained by washing with ethanol, filtering and drying.
[0050] (2) 0.5 g of the above-mentioned lithium lanthanum zirconium oxide powder modified with a coupling agent containing a double bond group, 1.4 g of acrylic acid, 3.7 g of ethyl acrylate, 4.2 g of styrene, 0.1 g of divinylbenzene, and 0.28 g of sodium dodecyl sulfate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 50°C, and then 0.2 g of hydrogen peroxide and 0.08 g of an aqueous solution of ferrous sulfate were added. After reacting for 2 hours, 0.1 g of hydrogen peroxide and 0.04 g of an aqueous solution of ferrous sulfate were added. The reaction was continued for 4 hours to obtain an organic-inorganic hybrid emulsion. Finally, 1 mol / L of an aqueous solution of lithium hydroxide was added dropwise to perform lithium neutralization to pH = 7-8 to obtain a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries with a solid content of 12 wt%.
[0051] The applicant further used the fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries of this embodiment in the preparation of the sulfur positive electrode of lithium-sulfur batteries and the silicon-carbon negative electrode of lithium-ion batteries, and further assembled the electrode pieces into button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells to test the lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode. The preparation of the sulfur positive electrode and silicon-carbon negative electrode, and the assembly method of the button-type lithium-sulfur battery and silicon-carbon negative electrode half-cell are the same as in Example 1.
[0052] Example 5
[0053] In this embodiment, a fast ion conductor interface capacity-enhancing ion conductive binder for lithium battery is provided, and the fast ion conductor interface capacity-enhancing ion conductive binder is prepared by the following steps:
[0054] (1) 2 g of lithium aluminum titanium phosphate was added to a mixture of 40 mL of ethanol and 1.2 mL of deionized water. After ultrasonic dispersion, 60 mg of diisopropyl diacryloyl titanate was slowly added dropwise under mechanical stirring. After reacting at 50 °C for 12 hours, the mixture was washed with ethanol, filtered, and dried to obtain lithium aluminum titanium phosphate powder modified with a coupling agent containing a double bond group.
[0055] (2) 0.5 g of the above-mentioned lithium aluminum titanium phosphate powder modified with a coupling agent containing a double bond group, 0.93 g of methacrylic acid, 4.8 g of butyl acrylate, 3.6 g of acrylonitrile, 0.1 g of 1, 4-butanediol diacrylate, and 0.28 g of sodium dodecyl sulfate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 50°C, and then 0.16 g of ammonium persulfate and 0.08 g of an aqueous sodium bisulfite solution were added. After reacting for 3 hours, 0.09 g of ammonium persulfate and 0.05 g of an aqueous sodium bisulfite solution were added. The reaction was continued for 3 hours to obtain an organic-inorganic hybrid emulsion. Finally, 1 mol / L of an aqueous lithium hydroxide solution was added dropwise to perform lithium neutralization to pH = 7-8 to obtain a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries with a solid content of 10 wt%.
[0056] The applicant further used the fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries of this embodiment in the preparation of the sulfur positive electrode of lithium-sulfur batteries and the silicon-carbon negative electrode of lithium-ion batteries, and further assembled the electrode pieces into button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells to test the lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode. The preparation of the sulfur positive electrode and silicon-carbon negative electrode, and the assembly method of the button-type lithium-sulfur battery and silicon-carbon negative electrode half-cell are the same as in Example 1.
[0057] Comparative Example 1
[0058] In this comparative example, an ion conductive adhesive is provided, and the ion conductive adhesive is prepared by the following steps:
[0059] 0.93 g of methacrylic acid, 4.8 g of butyl acrylate, 3.6 g of acrylonitrile, 0.1 g of divinylbenzene, and 0.23 g of sodium dodecyl sulfate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 50°C, and then 0.16 g of ammonium persulfate and 0.08 g of sodium bisulfite aqueous solution were added. After reacting for 3 hours, 0.09 g of ammonium persulfate and 0.05 g of sodium bisulfite aqueous solution were added. The reaction was continued for 2 hours to obtain a copolymer emulsion. Finally, 1 mol / L of lithium hydroxide aqueous solution was added dropwise for lithium neutralization to pH = 7-8 to obtain an ion conductive binder for lithium batteries with a solid content of 12 wt%.
[0060] The applicant further used the ion conductive binder for lithium batteries of this comparative example in the preparation of lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode pole pieces, and further assembled the pole pieces into button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells to test the lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode. The preparation of sulfur positive electrode pole pieces and silicon-carbon negative electrode pole pieces, and the assembly method of button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells are the same as in Example 1.
[0061] Comparative Example 2
[0062] In this comparative example, an organic-inorganic composite ion conductive binder for a lithium battery is provided, and the ion conductive binder is prepared by the following steps:
[0063] 0.5 g of unmodified lithium aluminum titanium phosphate powder, 0.93 g of methacrylic acid, 4.8 g of butyl acrylate, 3.6 g of acrylonitrile, 0.1 g of divinylbenzene, and 0.23 g of sodium dodecyl sulfate were added to deionized water and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature was raised to 50 ° C, and 0.16 g of ammonium persulfate and 0.08 g of sodium bisulfite aqueous solution were added. After reacting for 3 hours, 0.09 g of ammonium persulfate and 0.05 g of sodium bisulfite aqueous solution were added. After continuing to react for 2 hours, an organic-inorganic composite emulsion was obtained. Finally, 1 mol / L of lithium hydroxide aqueous solution was added dropwise for lithium neutralization to pH = 7-8 to obtain an organic-inorganic composite ion conductive binder for lithium batteries with a solid content of 12 wt%.
[0064] Figure 1 The scanning electron microscope photograph in b shows that the unmodified lithium aluminum titanium phosphate powder in the composite emulsion of Comparative Example 2 exhibits serious agglomeration, indicating that the unmodified lithium aluminum titanium phosphate powder has poor dispersibility in the binder.
[0065] The applicant further used the organic-inorganic composite ion conductive binder for lithium batteries in this comparative example in the preparation of lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode pole pieces, and further assembled the pole pieces into button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells to test the lithium-sulfur battery sulfur positive electrode and lithium-ion battery silicon-carbon negative electrode. The preparation of sulfur positive electrode pole pieces and silicon-carbon negative electrode pole pieces, and the assembly method of button-type lithium-sulfur batteries and silicon-carbon negative electrode half-cells are the same as in Example 1.
[0066] Verification Example
[0067] In this embodiment, the fast ion conductor interface compatibilizing ion conductive adhesives of Embodiments 1 to 5 and the adhesives used in Comparative Examples 1 and 2 were first tested for elongation at break and ionic conductivity, and the test results shown in Table 1 were obtained.
[0068] Table 1 Physical properties of ion conductive binders sample Elongation at break (%) Ionic conductivity (mS / cm) Example 1 191 0.25 Example 2 173 0.30 Example 3 205 0.13 Example 4 182 0.15 Example 5 191 0.18 Comparative Example 1 264 <0.01 Comparative Example 2 30 0.07 It can be seen from the data in Table 1 that the fast ion conductor interface compatibilizing ion conductive binders for lithium batteries of Examples 1-5 exhibit higher elongation at break and ion conductivity exceeding 0.1 mS / cm, which are higher than the ion conductivity of the binders in Comparative Examples 1 and 2. The simply mixed ion conductive binder in Comparative Example 2 forms a large number of defects in the adhesive film due to the uneven dispersion of the ion conductive filler, which leads to a significant reduction in the elongation at break and an imperfect conductive network; the ion conductive binder used in Comparative Example 1 has good uniformity and a higher elongation at break, but due to the lack of high-performance lithium ion conductive components, the ion conductivity is very low. In summary, neither of the two schemes in the comparative example can improve the electrochemical performance of lithium batteries well.
[0069] Furthermore, the applicant conducted rate performance tests and cycle performance tests on the lithium-sulfur batteries assembled in Examples 1-5 and Comparative Examples 1 and 2, and obtained the test results shown in Table 2.
[0070] Table 2 Electrochemical performance of lithium-sulfur batteries assembled with different ion-conductive binders sample <![CDATA[Discharge specific capacity at 0.1C (mAh g -1 )]]> <![CDATA[Discharge specific capacity at 25 °C (mAh g -1 ).]]> Capacity retention rate after 200 cycles (%) Example 1 1305 985 84.0 Example 2 1297 996 84.5 Example 3 1223 852 79.9 Example 4 1230 906 80.7 Example 5 1261 943 81.5 Comparative Example 1 1169 784 58.5 Comparative Example 2 1209 462 38.7
[0071] It can be seen from the data in Table 2 that the button-type batteries assembled with the fast ion conductor interface-enhanced ion conductive binder of Examples 1-5 have significantly higher rate performance than Comparative Examples 1 and 2. In addition, the cycle performance of the lithium-sulfur battery and silicon-carbon negative electrode half-battery assembled with the fast ion conductor interface-enhanced ion conductive binder of Examples 1-5 at different discharge rates is also higher than that of Comparative Examples 1 and 2. And the capacity retention rate of the button-type lithium-sulfur battery assembled with the ion conductor interface-enhanced ion conductive binder of Examples 1-5 after 200 cycles at 0.2 C is also much higher than that of Comparative Examples 1 and 2.
[0072] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, modifications and equivalent settings contained in the spirit and scope of the claims are all included in the scope of the present invention.
Claims
1. A fast ion conductor interface capacity increasing ion conductive binder for lithium battery, characterized in that: It is mainly formed by emulsion copolymerization and lithiation neutralization of four components A, B, C and D, wherein component A is an inorganic fast ion conductor powder modified by a coupling agent containing a double bond group, which is 3 to 10 parts by weight; component B is a lithiation-capable unsaturated monomer, which is 5 to 15 parts by weight; component C is an acrylate unsaturated monomer, which is 40 to 60 parts by weight; component D is an unsaturated monomer with excellent resistance to organic electrolytes, which is 25 to 45 parts by weight; The ionic conductivity of the fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries is higher than 0.1 mS / cm; The fast ion conductor interface capacity increasing ion conductive binder for lithium battery is prepared by the following method, comprising the following steps: (1) Adding an inorganic fast ion conductor powder to a mixture of ethanol and deionized water, and after ultrasonic dispersion, slowly adding a coupling agent containing a double bond group under mechanical stirring, reacting at 30-60°C for 12-36 hours, controlling the mass ratio of the inorganic fast ion conductor powder to ethanol to be 1:10-25, the mass ratio of the inorganic fast ion conductor powder to the coupling agent containing a double bond group to be 1:0.02-0.05, and the mass ratio of the coupling agent containing a double bond group to deionized water to be 1:10-15, and after the reaction is completed, washing with ethanol, filtering, and drying to obtain an inorganic fast ion conductor powder modified with a coupling agent containing a double bond group; (2) 3-10 parts by weight of an inorganic fast ion conductor powder modified with a coupling agent containing a double bond group, 5-15 parts by weight of a lithiation-capable unsaturated monomer, 30-60 parts by weight of an acrylate unsaturated monomer, 25-40 parts by weight of an organic electrolyte-resistant unsaturated monomer, 1-2 parts by weight of a cross-linking agent, and 2-5 parts by weight of a surfactant are added to deionized water, and stirred at high speed with a homogenizer to obtain a pre-emulsion. Under an argon atmosphere, the temperature is raised to 40-60° C., and then 2-3 parts by weight of a redox initiator is added. After reacting for 2-4 hours, 1-2 parts by weight of a redox initiator is added, and the reaction is continued for 2-4 hours to obtain an organic-inorganic hybrid emulsion. Finally, 0.5-2 mol / L of a lithium hydroxide aqueous solution is added dropwise to perform lithiation neutralization to pH=7-8, thereby obtaining a fast ion conductor interface capacity-enhancing ion conductive binder for lithium batteries having a solid content of 8 wt%-15 wt%.
2. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The inorganic fast ion conductor is one of lithium aluminum titanium phosphate, lithium lanthanum titanium oxide and lithium lanthanum zirconium oxide.
3. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The double bond group-containing coupling agent is one of vinyl dimethyl chlorosilane, vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri (β-methoxyethoxy) silane, and diisopropyl diacryloyl titanate.
4. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The lithiation-capable unsaturated monomer is one of acrylic acid, methacrylic acid and 2-ethylacrylic acid.
5. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The acrylic acid ester unsaturated monomer is one of ethyl acrylate, butyl acrylate and isooctyl acrylate.
6. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The unsaturated monomer with excellent resistance to organic electrolyte is one of styrene and acrylonitrile.
7. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The crosslinking agent is one of divinylbenzene, ethylene glycol diacrylate and 1,4-butanediol diacrylate.
8. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The emulsifier is one or more of sodium dodecyl sulfate, ammonium nonylphenol polyoxyethylene ether sulfate and sodium dodecylbenzene sulfonate.
9. The fast ion conductor interface capacity increasing ion conductive binder for lithium battery according to claim 1, characterized in that: The oxidizing component of the redox initiator is one of potassium persulfate, ammonium persulfate, and hydrogen peroxide; the reducing component of the redox system initiator is one of sodium thiosulfate, sodium bisulfite, and ferrous sulfate; the molar ratio of the oxidizing component to the reducing component of the initiator is 1:0.4~1.
Citation Information
Patent Citations
Lithium ion conductive binder and preparation method thereof, sulfide composite electrolyte membrane and preparation method thereof, and lithium battery
CN115340645A
PVDF (Polyvinylidene Fluoride)-based polyelectrolyte type lithium-sulfur battery binder as well as preparation method and application thereof
CN117625093A